An In Vivo Comparative Evaluation of Dental Anxiety Level and Clinical Success Rate of Composite and Multicolored Compomers in 6 to 12 years of Children - Hugar, Shivayogi M; Badakar, Chandrashekhar M; Thakkar, Prachi J; Kohli, Divyata (International journal of clinical pediatric dentistry, 2018)
Pediatric dentistry is not just about treating the tooth, but it also involves giving an overall comprehensive treatment to the child. Children like different colors and when the child is allowed to select the color of the restoration, it will positively motivate the child to accept dental treatment. The aim of our study was to evaluate and compare the clinical success rate of composite and multicolored compomer restorations and dental anxiety level in children. A total of 60 samples equally divided into two study groups by of split-mouth design. In the control group, subjects received composites and in experimental group, they received colored compomers. The dental behavior was assessed using the Frankl behavior rating scale for both the groups. Dental anxiety was checked in the patients using visual analogue scale (VAS) before and after the treatment for both the groups. Children were recalled for follow up at 1, 3 and 6 months to evaluate clinical success rate amongst control and experimental group and results were subjected to statistical analysis. Colored compomer proved to reduce the anxiety in the child and had a better behavioral response and positive attitude. Both restorative materials had comparable clinical success rates. At 6 months follow-up evaluation colored compomer restorative material showing promising with similar properties like that of composites with the added advantage of multicolors and can be considered as the new restorative material in the child dentistry. Colored compomers are known to be excellent alternative restorative materials for restoration of teeth in children as they aid in behavior modification and good compliance from the patient. Hugar SM, Kohli D, Badakar CM, Gokhale NS, Thakkar PJ, Mundada MV. An Comparative Evaluation of Dental Anxiety Level and Clinical Success Rate of Composite and Multicolored Compomers in 6 to 12 years of Children. International Journal of Clinical Pediatric Dentistry, 2018;11(6):483-489.